Multimodal Imaging in a Case of Fovea Plana Associated with Situs Inversus of the Optic Disc - Berrak Şekeryapan Gediz; Mehmet Ali Şekeroğlu (Türk Oftalmoloji Dergisi)

(untitled)
Fovea plana is a congenital condition characterized by anatomic absence of the foveal pit. It may be isolated or associated with congenital ocular anomalies. In this report, we present a case of fovea plana associated with situs inversus of the optic disc, optic disc hypoplasia, tilted optic disc, and prepapillary vascular loop and with best corrected visual acuity of 20/32. The aim of this report is to demonstrate the coexistence of very rare multiple optic disc anomalies and fovea plana, and also to emphasize that the use of multimodal imaging methods facilitates the identification of rare anomalies.